Baṅgīẏa Prādeśika Rāshṭrīẏa Sammelana, 1939 - Ghosh, Yatindrakumar (Adhyaẏana, 1979)
Comprises proceedings of a convention and newspaper reportage of a nationalist organization of Bengal during the Indian freedom movement.